Crack growth behavior at thermal fatigue of H13 tool steel processed by laser surface melting. (September 2015) - Jia, Zhi-xin; Liu, Yao-wei; Li, Ji-qiang; Liu, Li-Jun; Li, Hong-lin
Highlights: Two biomimetic specimens made by laser melting retard thermal crack growth. Specimen with the diamond-shaped pattern retards crack growth effectively. Microhardness decreases with increased thermal cycles. Grain size, hardness and layout of laser tracks influence crack growth. Abstract: Biomimetic specimens with striation-shape and diamond-shape morphologies were obtained by laser surface melting on an H13 die steel surface in quenched and tempered state using Nd:YAG laser. The thermal fatigue resistance behavior of the specimens with man-made crack sources was measured. For a set of number of thermal fatigue cycles, the two biomimetic specimens demonstrated decelerated crack growth that indicated better fatigue resistance as compared to the untreated one. The microstructures of the laser melting zone were finer than those of the untreated H13 specimen, and the microhardness of the former was higher than that of the latter after same number of thermal fatigue cycles.